2005
DOI: 10.1016/j.ejvs.2005.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Venous Insufficiency in Italy: The 24-cities Cohort Study

Abstract: Venous disease is very common in Italy, in particular in people living in the South. A correlation between varicose veins and venous incompetence is more marked in men, while minor objective and subjective symptoms prevail in women. The findings from this non-random sample closely match results from previous studies, in which random sampling was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
1
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 12 publications
1
65
1
11
Order By: Relevance
“…Age was recognised as the most important risk in early epidemiologic studies and also in recent epidemiologic studies, incorporated the CEAP classification, clinical and duplex evaluation into the study design 6,7 . Older cross sectional studies have been based on self-assessed diagnosis and the clinical classification of the varicose veins has not been adapted to the CEAP classification, which is now recommended.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age was recognised as the most important risk in early epidemiologic studies and also in recent epidemiologic studies, incorporated the CEAP classification, clinical and duplex evaluation into the study design 6,7 . Older cross sectional studies have been based on self-assessed diagnosis and the clinical classification of the varicose veins has not been adapted to the CEAP classification, which is now recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The role of obesity was controversial. Some studies have found increased the risk of varicose veins in overweight and obesity 3,8,9 but not other studies 6,7 . In addition, some studies have found different risk for women and for men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…II). Age is a well-known risk factor for the development of CVD [7], DVT [11] and also SVT [1,4]. Two recent prospective studies revealed age as a risk factor for SVT in CVD but only in patients with varicose veins.…”
Section: Discussionmentioning
confidence: 99%
“…19 KVY genel nüfusun %40'ını etkilemektedir. 20 Kronik venöz hastalıklar yüksek prevalansı nedeni ile büyük sosyoekonomik etkilere sebep olan yaygın bir durumdur. 21 Yapılan çalışmalara göre; kadınların %32, erkeklerin %40'ının varikoz venlere sahip olduğu, venöz hastalıkların herhangi bir tipinin erkeklerin %40-50'sini, kadınların ise %50-55'ini etkilediği görülmüştür.…”
Section: Kroni̇k Venöz Yetmezli̇ği̇n Anatomi̇si̇unclassified